Effect of tube processing methods on microstructure, mechanical properties and irradiation response of 14YWT nanostructured ferritic alloys. (1st August 2017) - Aydogan, E.; Maloy, S.A.; Anderoglu, O.; Sun, C.; Gigax, J.G.; Shao, L.; Garner, F.A.; Anderson, I.E.; Lewandowski, J.J.
Abstract: In this research, innovative thermal spray deposition (Process I) and conventional hot extrusion processing (Process II) methods have been used to produce thin walled tubing (∼0.5 mm wall thickness) out of 14YWT, a nanostructured ferritic alloy. The effects of processing methods on the microstructure, mechanical properties and irradiation response have been investigated by using scanning electron microscopy (SEM), transmission electron microscopy (TEM) and, micro- and nano-hardness techniques. It has been found that these two processes have a significant effect on the microstructure and mechanical properties of the as-fabricated 14YWT tubes. Even though both processing methods yield the formation of various size Y-Ti-O particles, the conventional hot extrusion method results in a microstructure with smaller, homogenously distributed nano-oxides (NOs, Y-Ti-O particles < 5 nm) with higher density. Therefore, Process II tubes exhibit twice the hardness of Process I tubes. It has also been found that these two tremendously different initial microstructures strongly affect irradiation response in these tubes under extremely high dose ion irradiations up to 1100 peak dpa at 450 °C. The finer, denser and homogenously distributed NOs in the Process II tube result in a reduction in swelling by two orders of magnitude. On the other hand, inhomogeneity of the initial microstructure in the Process I tube leads to large variations in both swelling and irradiation induced hardening. Moreover, hardening mechanisms before and after irradiation were measured and compared with detailed calculations. This study clearly indicates the crucial effect of initial microstructure on radiation response of 14YWT alloys. Graphical abstract: